Analyzing the Influence of Service Quality in Water Distribution on Customer Complaints and Its Role in Enhancing Customer Satisfaction - Kusuma, Gusti Putu Eka; I Gusti Made Oka Astana; Ningsih, Ni Nyoman Ayu; Cattleyana, Dilla; Mustafa, Zainol (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the impact of water distribution service quality on customer complaints as part of efforts to enhance customer satisfaction at Perumda Air Minum Tirta Hita Buleleng. A quantitative approach was employed, with data collected through questionnaires. The questionnaire responses were measured using an interval scale. Respondents were selected using random sampling techniques. The data were analyzed using SmartPLS software. The study explored three main relationships: the influence of water distribution service quality on customer complaints, the influence of water distribution service quality on customer satisfaction, and the influence of customer complaints on customer satisfaction. The findings indicate that all relationships examined are positive and significant, highlighting the critical role of service quality in reducing complaints and improving customer satisfaction.